Theoretical study of the mechanism and kinetics of the atmospheric reaction of acrylic acid with NO3 radical. Issue 4 (28th October 2022) - Sun, Jingyu; Xiao, Weikang; Tang, Yizhen; Zhang, Yunju
Abstract: The nitrate radical is one of the most significant oxidants in troposphere at the nighttime. Furthermore, acrylic acid is reported to be one of 189 hazardous air pollutants. In order to investigate the atmospheric chemistry and environmental impact of acrylic acid with nitrate radical, in this work, the atmospheric reaction mechanisms of acrylic acid by NO3 radical have been discussed by the CCSD(T)/cc‐pVTZ//M06‐2X/6‐311++G(d, p) dual‐level of theory at the first time. The energy barriers of NO3 and CH2 CHCOOH reaction have also been calculated accurately. The additions between NO3 with CH2 CHCOOH would produce the dominant intermediates CH2 NO3 CHCOOH and CH2 CHNO3 COOH via low barriers. All hydrogen abstraction channels have higher barriers than that of additions. Therefore, addition pathways play an important role in this reaction. The total and branching rate constants have been computed by conventional transition state theory via the Variflex code. These rate constants of NO3 and acrylic acid reaction would be useful to complete structure–activity relationships of reaction rate. The calculated atmospheric lifetime of acrylic acid by NO3 is about 3.66 days at night. All findings will help us gain a better understanding of atmospheric chemistry of acrylic acid. Abstract : Addition pathways are dominant for the reaction of acrylic acid with nitrate radical. The addition intermediate of terminal carbon atom of C=C bond of acrylic acid are the most important product. The pre‐reactive complexes are considered in the rate constant calculations. The total and branching rate constants have been calculated.